What Al-Qasimi attributed to most of the commentators in his interpretation, “Muhsin al-Tawil,” is a balanced study - Assis. lectu. Zainab Akram Qasim; Assis. lectu. Wajdan Karim Ayay (Journal of College of Education, 2025)
This research deals with a comparative study between Sheikh Muhammad Abdullah Al-Qasimi’s interpretation in “Mahasin Al-Ta’wil” and the interpretations of other interpreters, reviewing how Al-Qasimi attributed their opinions and ideas in interpreting the Quranic verses. A number of verses that Al-Qasimi relied on were analyzed, while comparing his interpretation with the interpretations of scholars such as Ibn Kathir, Al-Tabari, and Al-Zamakhshari. The research showed that Al-Qasimi followed a balanced approach that combined accuracy in understanding the texts and depth in analysis, while relying on the predecessors and presenting new visions in some topics. The rhetorical and linguistic style used by Al-Qasimi was also highlighted, which made him stand out as one of the distinguished interpreters of his time The results confirmed that “Mahasin al-Ta’wil” is not limited to merely conveying opinions, but rather provides a comprehensive interpretation that reflects a deep understanding of the objectives of the Shari’ah. Ultimately, the research enhances the value of Al-Qasimi’s interpretation as a primary source in Qur’anic studies, and calls for further academic studies that explore the various aspects of this pioneering work.